2003
DOI: 10.1042/cs20030033
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of vascular and renal mitogen-activated protein kinases in hypertensive rats is normalized by inhibitors of the Na+/Mg2+ exchanger

Abstract: In the present in vivo study, we have investigated whether inhibitors of the Na(+)/Mg(2+) exchanger quinidine and imipramine influence the development of hypertension and whether this is associated with modulation of mitogen-activated protein (MAP) kinase activation in arteries and kidneys of hypertensive rats. Sprague-Dawley rats were divided into four groups (n =6/group): control (vehicle), angiotensin II (Ang II; 150 ng/kg of body weight per min subcutaneously), quinidine [Ang II (150 ng/kg of body weight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…38 Another mechanism whereby aldosterone may influence urinary Mg 2ϩ excretion is through the Na ϩ /Mg 2ϩ exchanger, which we demonstrated to be upregulated in hypertension. 39 Hence altered Mg 2ϩ metabolism in hyperaldosteronism may be related to direct stimulation of the Na ϩ /Mg 2ϩ exchanger on the one hand and to downregulation of TRPM7 on the other.…”
Section: Discussionmentioning
confidence: 99%
“…38 Another mechanism whereby aldosterone may influence urinary Mg 2ϩ excretion is through the Na ϩ /Mg 2ϩ exchanger, which we demonstrated to be upregulated in hypertension. 39 Hence altered Mg 2ϩ metabolism in hyperaldosteronism may be related to direct stimulation of the Na ϩ /Mg 2ϩ exchanger on the one hand and to downregulation of TRPM7 on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in accordance with previous studies that associate JNK activation with increased levels of oxidative stress and ROS-mediated cell death. 34 In particular, JNK is known to play a major role in cardiovascular disease and is activated on mechanical stress, hypertension, [11][12][13] and ischemia/reperfusion. 35 JNK has also been reported to be activated in advanced atherosclerotic plaques in rabbits as well as in humans 34 and to activate matrix proteases involved in disease progression of abdominal aortic aneurysm in mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies using gene targeting as well as JNK inhibitors demonstrated the involvement of JNK1 and JNK2 genes in several pathological conditions including cancer, immune diseases, and neurological diseases as well as metabolic disorders and inflammatory conditions such as arthritis and atherosclerosis. 10 JNKs are expressed in vascular smooth muscle cells and endothelial cells and activated by a wide range of stimuli such as oxidative stress, mechanical stretch, hypertension, [11][12][13] hyperglycemia, apoptosis, 14 and inflammation. 10 A recent study suggested a role of JNK in endothelial dysfunction: short-term exposure of coronary arterioles to tumor necrosis factor-␣-induced endothelial dysfunction through activation of JNK signal transduction pathway and generation of superoxide anion.…”
Section: Clinical Perspective P 2080mentioning
confidence: 99%
“…In theory, such reductions in activity could be mediated by PKC and/or mitogen-activated protein kinase (MAPK) (3,19,37). Past studies have shown that both phosphotransferases are upregulated in the hypertensive state (23,36). If these signaling proteins are indeed enhanced in feed arteries from hypertensive hamsters, it is reasonable to assume that their most observable impact on cell-to-cell communication would occur under experimental conditions that ensure their robust activation.…”
Section: Hypertension and Cell-to-cell Communicationmentioning
confidence: 99%